2002
DOI: 10.1055/s-0037-1613057
|View full text |Cite
|
Sign up to set email alerts
|

No Association of Plasma Prothrombin Concentration or the G20210A Mutation with Incident Cardiovascular Disease

Abstract: SummaryProthrombin is a key factor in blood clotting, a process intimately involved in thrombotic disease. We assessed prothrombin levels and G20210A genotype in a case-control study within the Cardiovascular Health Study. Cases included angina, myocardial infarction, stroke, and the presence of MRI-detectable infarcts (n ≈ 250 each). Populationbased controls free of clinical cardiovascular disease (CVD) (n ≈ 500) and a subset free of clinical and subclinical CVD (n ≈ 250) were used for comparison. The 20210 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 50 publications
1
22
0
7
Order By: Relevance
“…In a previous nested case-control study of the Cardiovascular Health Study, no association was found between prothrombin (factor II) levels and incident or prevalent myocardial infarction9). Small case-control studies (n=22 to 300) suggested that factors V and XI were possibly associated with CHD1012), and factors II, X, and XII were not10,11), generally consistent with our findings.…”
Section: Discussionmentioning
confidence: 91%
“…In a previous nested case-control study of the Cardiovascular Health Study, no association was found between prothrombin (factor II) levels and incident or prevalent myocardial infarction9). Small case-control studies (n=22 to 300) suggested that factors V and XI were possibly associated with CHD1012), and factors II, X, and XII were not10,11), generally consistent with our findings.…”
Section: Discussionmentioning
confidence: 91%
“…Its association with arterial stroke remains controversial. This mutation has not been associated with acute ischemic stroke either in larger case-control or in prospective cohort studies [39,40].…”
Section: Coagulation and Fibrinolytic Factors And Ischemic Strokementioning
confidence: 84%
“…Periostin knockout (Pn −/− ) mice have an increased rate of ventricular rupture after myocardial infarction 36 , but increased periostin expression is also seen in ventricular hypertrophy and fibrosis 37 . In addition, prothrombin itself has been linked to CVD, associated with an increased risk of venothrombotic disease 38 but not arterial disease 39 .…”
Section: Discussionmentioning
confidence: 99%